Deteksi Bakteri Patogen Pada Daging Ayam Broiler Sebagai Skrining Foodborne Diseases Di Kabupaten Jember - Suswati, Enny; Supangat, Supangat; Lutfadaturroifa, Alya Wafaul; Pratama, Dava Rizky (Jurnal Sain Veteriner, 2024)
Chicken meat is a source of animal protein that is very popular because of its high nutritional value, easy to obtain and cheap. However, as production increases, certain drugs and feed additives become essential for disease prevention, treatment, and growth promotion. The negative effect of using antimicrobial drugs is that they accumulate in animal tissues as residues and eventually become part of the food pyramid, subsequently impacting human health.A total of 45 broiler chickens were purchased from broiler meat sellers in 9 traditional markets in Jember. We took five broiler chicken meat randomly from each market. Samples have identified the type of contaminant bacteria using Salmonella Chromogenic Agar and Mannitol Salt Agar. The results of this study showed that broiler chicken meat samples were contaminated with E. coli (45/45 (100%)), Staphylococcus aureus (43/45 (95.56%)), Salmonella spp. (38/45 (84.44%)) and Proteus spp. (14/45 (33.33%)). All broiler meat samples purchased at the Jember traditional market were contaminated with at least 1 type of bacteria, namely E. coli. The index of bacterial contamination is between 0.25 – 1. The most common contamination patterns are S. aureus, E. coli and Salmonella spp., with a bacterial contamination index of 0.75.